PERCEPTION OF UNDERSTANDING ABILITY OF REDOX CONCEPT ON STUDENT E-LEARNING OUTCOMES - Siti Suryaningsih; Nadiyah Aulia Rahmah; Fauzan Aldiansyah (Jurnal Ilmiah Didaktika, 2022)
The application of e-learning greatly impacts the ability to understand concepts and student learning outcomes. The purpose of the study was to determine 1) the prerequisite test of research instruments 2) the perception of the ability to understand redox concepts in e-learning based on indicators of learning stimuli, responses, and evaluations. 3) the relationship of understanding redox concepts to student learning outcomes. The method used is descriptive quantitative, in-class X MIA at MAN Tangerang, 38 students were selected by purposive random sampling. Data collection was carried out through a questionnaire using a Likert scale. The results showed that the prerequisite test was declared valid, reliable, and normally distributed. Student perceptions generally agree based on learning stimulus indicators as much as 71.025%; response 71.075%; evaluation 62.475%. Students give full attention during learning, participate actively during discussions, and understand redox concepts. Understanding redox concepts on student learning outcomes has a significant relationship (strong and positive), seen from the value of sig. (2-tailed) of 0.000 less than 0.05, Pearson correlation of 0.967 greater than 0.329 (significance 5%). The results of this study serve as scientific information on e-learning for chemistry subject teachers in improving the learning process.